Cinematic landscapes, dark tourism and the ghosts of Port Arthur. Issue 4 (2nd October 2019) - Findlay, James
Abstract: Since its closure in the late nineteenth century, Port Arthur has emerged as one of Australia's most important heritage sites. This article considers cinema's role in its evolution from former penal settlement to popular travel destination by exploring a series of travelogue films produced between the 1930s and 1950s. These films were unique for Tasmanian tourism promotion of the period because they encouraged visitors to actively remember the site's convict past. Furthermore, their representations of the convict experience drew on audiences' prior knowledge of Port Arthur's role as a major film location in earlier silent features, helping to characterise it as a site of dark tourism and informing visitors' experiences and expectations on the ground. Ultimately these telling screen encounters illustrate how cinema prompted Australians to confront contentious convict histories with regard to their role in tourism, identity and place. This article was the winner of the 2017 Jill Roe Prize awarded by the Australian Historical Association for the best unpublished article-length work of historical research in any area of historical enquiry produced by a postgraduate student.